Recent advances in tumor targeted polymeric nanoparticles for HNC treatment: Enhancing therapeutic efficacy via engineered and biocompatible drug delivery systems - Manoj Kumar Srinivasan; Monisha Prasad (Journal of Oral Biology and Craniofacial Research)
Head and neck cancer (HNC) represents a heterogeneous group of malignancies with high global incidence and mortality rates. Traditional treatments for advanced HNC, such as combined radiotherapy and chemotherapy, often lead to debilitating long-term side effects that significantly affect patients quality of life. In response to these limitations, tumor-targeted polymer-based nanoparticles have emerged as a promising strategy to improve therapeutic efficacy while minimizing adverse effects. Polymeric nanoparticles comprised of natural or synthetic polymers and sized between 10 and 1000 nm have several benefits, including biocompatibility, adaptable drug release patterns, and the capacity to improve the solubility and stability of medicinal compounds. These nanoparticles can be engineered to target medications to tumor sites specifically, lowering systemic toxicity and enhancing treatment results. This review focuses on recent advances in the targeted therapy of HNC using polymeric nanoparticles such as chitosan, alginate, cyclodextrin, poly (lactic acid), poly (caprolactone), poly (ethylene glycol), dendrimers, and micelles. The emphasis is on their mechanisms, advantages, and potential to transform present HNC treatments.